2014
DOI: 10.1002/lt.23804
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the predictive score for 6-month graft survival in living donor liver transplantation in the modern era

Abstract: The limitations of donor age, graft size, and the Model for End-Stage Liver Disease (MELD) score have not been apparent in living donor liver transplantation (LDLT). Our team developed a formula for predicting graft survival after LDLT; the formula includes the graft weight, donor age, MELD score, and portosystemic shunt status. The aims of this study were to re-evaluate the reliability of our formula and to assess whether our modified treatment strategy has improved 6-month graft survival. Two hundred sevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…Liver transplantation with a donor graft weighing less than the minimal GW should be considered an absolute contraindication for partial liver transplantation, and the living donor should be changed to another appropriate donor or deceased whole liver donor. Previous reports from our group (12,13) and other groups (28)(29)(30)(31)(32) have shown that the risk factors for EGL include MELD score, graft volume, donor age, and others. We developed the previous results (12,13) with more data in this study, focusing on the preoperatively assessable variables.…”
Section: Discussionmentioning
confidence: 74%
“…Liver transplantation with a donor graft weighing less than the minimal GW should be considered an absolute contraindication for partial liver transplantation, and the living donor should be changed to another appropriate donor or deceased whole liver donor. Previous reports from our group (12,13) and other groups (28)(29)(30)(31)(32) have shown that the risk factors for EGL include MELD score, graft volume, donor age, and others. We developed the previous results (12,13) with more data in this study, focusing on the preoperatively assessable variables.…”
Section: Discussionmentioning
confidence: 74%
“…Our group previously showed that higher recipient BMI was associated with significantly worse outcomes after LDLT. 24 Therefore, at Kyushu University, eligibility for LDLT recipients and donors was restricted to those with BMI preferably less than 30 kg/m 2 . So, more stringent eligibility criteria for undergoing LDLT might have contributed to better survival after LDLT.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the remnant factors including lower graft quality (ie, donor age of ≥48 years), increased metabolic demand (ie, MELD score of ≥19), and over‐inflow (ie, PVP of ≥ 19 mm Hg at the end). Such factors should much more strongly affect the clinical outcomes of LL‐LDLT than whole liver transplantation because of the smaller number of hepatic cells in LL‐LDLT, and LL grafts should be considered as possibly marginal grafts …”
Section: Discussionmentioning
confidence: 99%